Bahasa Indonesia - Wahyuni, Ni Kadek Sri Yunia; Ekawati, Ni Wayan (E-Jurnal Manajemen; Vol 7 No 5 (2018)DO - 10.24843/EJMUNUD.2018.v07.i05.p20, 2018)
Along with the growing business growth in shipping services, it creates intense competition, so in order to survive and win the company customers are required to optimize the quality of service and satisfy its customers. Therefore this study aims to determine the effect of service quality on word of mouth mediated by customer satisfaction variables. Population in this research is society which have used service delivery of TIKI. This research was conducted in Denpasar with sample of 110 respondents. Data analysis techniques used consist of path analysis and Sobel Test. The results showed that service quality and customer satisfaction had positive and significant effect on word of mouth. Customer satisfaction is significantly able to mediate the relationship between service quality to word of mouth. This result confirms that good service quality can increase consumer satisfaction of a service with so satisfied consumer will influence other consumer through word of mouth.